2016
DOI: 10.1038/ncomms10841
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: Delivery of crop pollination services is an insufficient argument for wild pollinator conservation

Abstract: Nature Communications 6: Article number: 7414 (2015); Published: 16 June 2015; Updated: 18 February 2016. The authors inadvertently omitted Kimiora L. Ward, who managed and contributed data, from the author list. This has now been corrected in both the PDF and HTML versions of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Furthermore, generalists are more likely to take advantage of crop species in agricultural landscapes ( Hopfenmüller, Holzschuh & Steffan-Dewenter, 2020 ; Leong, Kremen & Roderick, 2014 ). In their meta-analysis of studies conducted globally on crop-visiting pollinators, Kleijn et al (2016) found that the species pool in agricultural systems is made-up of a small subset of dominant species. Furthermore, dominant crop pollinators persist under agricultural expansion and can easily be enhanced by simple conservation measures, but threatened species are rarely observed on crops ( Kleijn et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, generalists are more likely to take advantage of crop species in agricultural landscapes ( Hopfenmüller, Holzschuh & Steffan-Dewenter, 2020 ; Leong, Kremen & Roderick, 2014 ). In their meta-analysis of studies conducted globally on crop-visiting pollinators, Kleijn et al (2016) found that the species pool in agricultural systems is made-up of a small subset of dominant species. Furthermore, dominant crop pollinators persist under agricultural expansion and can easily be enhanced by simple conservation measures, but threatened species are rarely observed on crops ( Kleijn et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In their meta-analysis of studies conducted globally on crop-visiting pollinators, Kleijn et al (2016) found that the species pool in agricultural systems is made-up of a small subset of dominant species. Furthermore, dominant crop pollinators persist under agricultural expansion and can easily be enhanced by simple conservation measures, but threatened species are rarely observed on crops ( Kleijn et al, 2016 ). Similar patterns of generalization have been observed in urban landscapes ( Leong, Kremen & Roderick, 2014 ; Lowenstein, Matteson & Minor, 2019 ), however urban landscapes also act as a refuge for certain guilds of pollinators ( Wenzel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…O manejo ecológico de solo é uma alternativa para melhorar o desempenho agrícola, mitigando os efeitos gerados pela agricultura convencional na agrobiodiversidade (FALCÃO, 2015). Além disso, auxilia na conservação dessa biodiversidade fundamental para manter diversos serviços ecossistêmicos (KLEIJN, 2015), sendo considerado uma ferramenta chave no processo de transição agroecológica para auxiliar o restabelecimento da biodiversidade agrícola.…”
Section: Resiliência Dos Serviços Ecossistêmicosunclassified
“…One of the Super-B working groups, WG4, addressed the possible drivers for the decline in bee numbers and diversity in Europe, one of which was identi ed as the transmission of parasites and pathogens between bee species 4,5 . The increasing homogenization of the agricultural landscapes across Europe is re ected in the loss of pollinators in these landscapes [6][7][8][9] , with most of the pollination services provided by a few dominant bee species 6,8 . The key question is whether, and to what extent, such changes in the communities of pollinators are related the distribution and transmission of parasites and pathogens between bee species [10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%